2012
DOI: 10.1128/cvi.00056-12
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Variola and Vaccinia Virus Neutralization Assays for Smallpox Vaccines

Abstract: P revious studies (6) suggested that the quantitative titers of human serum plaque reduction neutralization tests (PRNTs) differed when variola or vaccinia virus was used as the neutralization target. Similar observations were made during Acambis2000 vaccine studies in postimmunization nonhuman primate sera (10). This study was designed to evaluate the correlation between PRNTs when different virus species or strains were used as the neutralization target. This study is the first to look extensively at these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…However, a two-dose regimen of IMVAMUNE ® has been shown to provide a similar antibody response as Dryvax ® [9], reduced the size of replicating vaccinia takes [9,28] and was as effective if not better than Dryvax ® in producing peak 90% variola virus neutralization GMTs [39,40]. The two-dose SC MVA regimen remains the standard against which other regimens/doses are compared until more data are available.…”
Section: Discussionmentioning
confidence: 94%
“…However, a two-dose regimen of IMVAMUNE ® has been shown to provide a similar antibody response as Dryvax ® [9], reduced the size of replicating vaccinia takes [9,28] and was as effective if not better than Dryvax ® in producing peak 90% variola virus neutralization GMTs [39,40]. The two-dose SC MVA regimen remains the standard against which other regimens/doses are compared until more data are available.…”
Section: Discussionmentioning
confidence: 94%
“…Serum from the same clinical trial was used to correlate between PRNTs when different viruses and different strains of virus were used as the neutralization target. Use of Dryvax as the neutralization target resulted in significantly lower 90% PRNTs than use of variola as the neutralizing target and use of MVA resulted in significantly higher PRNTs than using variola [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Keasey et al observed greater increases in antibody responses to several MPXV proteins than to VACV proteins by aerosol MPXV-challenged macaques (59), indicating that although broad cross-reactivity exists, a stronger response may be directed toward MPXV-specific proteins. Differences in neutralization titers have also been observed, depending on the strain of OPV utilized in the PRNT assays (68,69). While a direct comparison between titration methods is not possible using the vaccinia virus-based HCS-GFP assay, future experiments that shed light on the virus specificity of this broader response and the virus-specific neutralization capacity after vaccination and challenge would be of interest.…”
Section: Discussionmentioning
confidence: 99%